Opioid Prescribing Patterns After Skull Base Surgery for Vestibular Schwannoma. Issue 1 (January 2022) - Ren, Yin; Mehranpour, Pasha; Moshtaghi, Omid; Schwartz, Marc S.; Friedman, Rick A.
Abstract : Objective: Excessive opioid prescription is a source of prescription diversion and could contribute to chronic opioid abuse. This study describes the opioid prescribing patterns and risk factors for additional opioid prescription after surgical resection of vestibular schwannoma (VS). Study Design: Retrospective chart review. Setting: Single tertiary referral center. Patients: Adult VS patients undergoing surgical resection between May 2019 and March 2020. Interventions: Opioid use postoperatively and up to 60 days following surgery were characterized from medical records and by querying the state-wide Controlled Substance Utilization Review and Evaluation System. Main Outcome Measures: The presence of additional opioid prescriptions within 60 days of surgery. Results: A total of 109 patients (mean age 50 yrs, 65.5% female) were prescribed an average of 138.2 ± 117.8 mg of morphine equivalents (MME). Twenty-two (20.9%) required additional prescriptions of 163.2 ± 103.2 MME. Age, gender, tumor size, or surgical approach (translabyrinthine, retrosigmoid, versus middle fossa) were not associated with additional prescriptions. Patients with additional prescriptions had higher body mass index (BMI 28.8 vs. 25.8 kg/m 2, p  = 0.015) and required more opioid medications during hospitalization (51.8 vs. 29.1 MME, p  = 0.002). On multivariate logistic regression, higher BMI (odds ratio [OR] 1.32; p  = 0.001), history of headaches (OR 11.9, p  = 0.011), and history of opioid use (OR 29.3, p  = 0.008) were associated with additional prescription. Conclusions: Additional opioid prescriptions may be necessary in a portion of VS patients undergoing surgery. The choice of surgical approach is not associated with excess opioid requirements. Patients with higher BMI, history of headaches, or preoperative opioid use may require additional prescriptions.